Parental burnout, depression and emotional development of the preschoolers - Yakupova, Vera; Suarez, Anna (Frontiers in Psychology, 2023)
Introduction Parental burnout is becoming more and more prevalent in the world, mainly incultures with high demands towards parents. Parental burnout is distinctive from depression and might have its unique influence on child development, which isunder current international research. This work contributes to the understanding of parental burnout, maternal depression and child emotional development(specifically emotion comprehension) interrelations. Additionally, we explored whether there are differences in the effects of parental burnout and depressionon boys and girls. Methods To analyse the emotional development of the preschoolers, the Russian version of the Test of Emotional Comprehension (TEC) was used. We used the Russian version of the Parental Burnout Inventory (PBI) to analyse the level of PB and the Russian version of Beck depression Inventory (BDI) to assess participants’ depression level. Results Parental burnout positively correlates with child emotional comprehension skills, specifically understanding of external causes (B = 0.20, CI: 0.03; 0.37) and mental causes of emotions (B = 0.22, CI: 0.05; 0.40). This effect is gender dependent and is significantlyhigher for girls (B = 0.54, CI: 0.09; 0.98). The effect of maternal depression on emotion comprehension skills is also gender dependent: total scores on emotioncomprehension tasks are significantly higher for daughters of mothers with depression (B = 0.59, CI: 0.001; 1.18). Discussion Maternal depression and parental burnout might provoke development of extra sensitivity and self-regulation strategies in girls.